Combination Therapy with Nintedanib and Sarilumab for the Management of Rheumatoid Arthritis Related Interstitial Lung Disease. (9th March 2020) - Vacchi, Caterina; Manfredi, Andreina; Cassone, Giulia; Salvarani, Carlo; Cerri, Stefania; Sebastiani, Marco
Abstract : Rheumatoid arthritis (RA) is a chronic, systemic, inflammatory disease characterized by joint and extra-articular involvement. Among them, interstitial lung disease (ILD) is one of the most common and severe extra-articular manifestations, with a negative impact on both therapeutic approach and overall prognosis. ILD can occur at any point of the natural history of RA, sometimes before the appearance of joint involvement. Since no controlled studies are available, the therapeutic approach to RA-ILD is still debated and based on empirical approaches dependent on retrospective studies and case series. Here, we report the case of a 75-year-old patient affected by RA complicated by ILD successfully treated with a combination therapy of an antifibrotic agent, nintedanib, and an inhibitor of IL-6 receptor, sarilumab. We obtained a sustained remission of the joint involvement and, simultaneously, a stabilization of the respiratory symptoms and function, with a good safety profile. To date, this is the first report describing a combination therapy with nintedanib and a disease-modifying antirheumatic drug (DMARD) for the management of RA complicated by ILD. Future prospective studies are needed to better define efficacy and safety of this approach in the treatment of these subjects.